KRITERIA PENYAKIT TANAMAN KARET DENGAN METODE FORWARD CHAINING BERBASIS WEBSITE: Expert System, Forward Chaining, Diagnosis, Diseases of Rubber Plants - Mulyadi; Natia Utari, Dini (LP2M Universitas Nurdin Hamzah, 2023)
Like most plantation crops in general, rubber can be attacked by various diseases originating from fungi, pests, animals and even cancer cells. For that we need a method that is able to diagnose rubber disease. In previous studies related to plant disease diagnoses, among others, using the forward chaining method, certainty factor method and forward chaining. This study develops an analysis of the results of the diagnosis of rubber plant diseases using the expert system method. The choice of this method states that the Expert System method is capable of intuitively resembling the way the human brain works. With this method, it is hoped that the diagnosis of rubber plant diseases can assist farmers in detecting symptoms earlier so that the productivity of rubber plantations can be achieved. increase. The results of the research in the calculations carried out to diagnose rubber plant diseases, as many as 161 rubber plant object data are complemented by 33 identity symptoms and diagnoses from plantation data, then testing 60 rubber plant data without a diagnostic label, the accuracy value is obtained. of 81.28%. Likewise, testing by randomizing training data with Cross Validation obtained close results.